2014
DOI: 10.1111/1755-5922.12063
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Interatrial Block is Associated with Recurrence of Atrial Fibrillation Post Pharmacological Cardioversion

Abstract: SUMMARYIntroduction: Management of atrial fibrillation (AF) is hampered by frequent recurrences after restoration of sinus rhythm. Delayed interatrial conduction has been associated with the development of AF in different clinical settings. The aim of our study was to assess whether advanced interatrial block (aIAB) was associated with AF recurrence after pharmacological cardioversion with two different antiarrhythmic drugs. Methods: We included 61 patients with recent onset AF without structural heart disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 32 publications
4
31
0
8
Order By: Relevance
“…A multivariate analysis found IAB to be independently associated with AF recurrence (odds ratio [OR], 18.4). The study confirms that advanced IAB is strongly associated with a higher risk of AF recurrence 1 year following pharmacological cardioversion, independent of the antiarrhythmic drug used [25].…”
Section: Iab As a Predictor Of Supraventricular Arrhythmias In Differsupporting
confidence: 75%
“…A multivariate analysis found IAB to be independently associated with AF recurrence (odds ratio [OR], 18.4). The study confirms that advanced IAB is strongly associated with a higher risk of AF recurrence 1 year following pharmacological cardioversion, independent of the antiarrhythmic drug used [25].…”
Section: Iab As a Predictor Of Supraventricular Arrhythmias In Differsupporting
confidence: 75%
“…46,14 The higher prevalence in the aforementioned studies likely is due to the populations examined (e.g., those with structural heart disease). In contrast, we observed a lower prevalence in the ARIC study, as this community-based population is not limited to participants with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Additionally, aIAB has been associated with a higher risk of AF recurrence after pharmacological cardioversion to normal sinus rhythm. 6 To date, the association between aIAB and AF has not been examined in prospective population-based studies. Therefore, the purpose of this analysis was to examine the prevalence and incidence of aIAB as well as the association between aIAB and AF in the Atherosclerosis Risk In Communities (ARIC) study, a community-based prospective cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The delayed and heterogeneous activation of the LA results in dispersion of atrial refractory periods, interatrial dyssynchrony and impaired LA mechanical function, 19,20 all of which favor the development of AF. Thus, IAB (partial or advanced) has been found to be associated with new-onset AF in patients from a general hospital population, 21 , recurrence of AF postelectrical or pharmacological cardioversion, 22,23 , AF recurrence after pulmonary vein isolation, 24 and progression of paroxysmal AF to the persistent or permanent forms of the disease. 25,26 In patients with CHF, the association of Pwave abnormalities with development of AF was first described by Yamada et al 15 using signal averaged ECG (SAECG).…”
Section: Discussionmentioning
confidence: 99%
“…4 The presence of aIAB is frequently associated with atrial tachyarrhythmias and has been found to be a predictor of AF in different clinical scenarios. [5][6][7] The aim of this study was to determine whether the presence of aIAB is a predictor of new onset AF in patients with advanced CHF undergoing cardiac resynchronization therapy (CRT).…”
mentioning
confidence: 99%